2014
DOI: 10.1007/s00405-014-2936-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative free jejunum flap monitoring with indocyanine green near-infrared angiography

Abstract: The free jejunum flap technique has been regarded as the optimal approach during circumferential pharyngolaryngectomy reconstruction.Although classical patency tests are available, an intraoperative guarantee of the patency of anastomoses and microcirculations is inevitable.Indocyanine green near-infrared angiography (ICGA) was intraoperatively performed in six patients after reconstruction using the free jejunum flap.An adequate arterial as well as venous phase were observed. In addition to classical patency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…28 In a study on free jejunum transfer after circumferential pharyngolaryngectomy, it was highlighted that the value of postoperative monitoring of buried free flaps after wound closure is more predictive than intraoperative monitoring in identifying vascular compromise. 27 This increases the guarantee of flap survival, particularly in high-risk patients, 41 and salvage reconstruction. 42 Recently, ICG angiography has also been used in assessing successful free nerve grafting to the head and neck.…”
Section: Icg Angiography: Results By Indication and Type Of Flap Freementioning
confidence: 99%
“…28 In a study on free jejunum transfer after circumferential pharyngolaryngectomy, it was highlighted that the value of postoperative monitoring of buried free flaps after wound closure is more predictive than intraoperative monitoring in identifying vascular compromise. 27 This increases the guarantee of flap survival, particularly in high-risk patients, 41 and salvage reconstruction. 42 Recently, ICG angiography has also been used in assessing successful free nerve grafting to the head and neck.…”
Section: Icg Angiography: Results By Indication and Type Of Flap Freementioning
confidence: 99%
“…Conventionally, intraoperative evaluation of blood flow to organs was based on the color tone of the organs wall and the presence or absence of bleeding and arterial pulsation. However, ICG fluorescence imaging, which observe the organs using a camera with near-infrared light after intravenous injection of ICG, can confirm blood flow to organs with fluorescence, clearly delineating the boundary between areas with good and poor perfusion [ [8] , [9] , [10] , [11] ]. In our case, ICG fluorescence imaging was performed to visualize the blood flow and vascular distribution in the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Compromised arterial supply and venous drainage cause postoperative complications, such as flap necrosis. 21,22 Murono et al 21 found that the intrinsic transit time of the flap, which was defined as the period from when the dye appeared at the arterial anastomosis until it reached the suture line of the venous anastomosis, was $10 seconds in six free jejunum flaps. Holzbach et al 23 90.0 seconds is a suggested threshold for identifying venous delay and pre-emptively assisting venous drainage via supercharging.…”
Section: Intraoperative Application Of Icg Intraoperative Evaluation mentioning
confidence: 99%
“…We found 29 articles introducing a potential dosing protocol for ICG (►Fig. 2), 1,11,16,21,22,[26][27][28][29][31][32][33]35,39,[44][45][46][47][48][49][50][51][52][53][54][55][56] and a total dose of 12.5 mg was the most frequently used intravenous dose. The second and third most frequently used intravenous doses were 7.5 mg total and 0.5 mg/kg (weight) , respectively.…”
Section: The Security Of Applying Icg In Flap Surgerymentioning
confidence: 99%
See 1 more Smart Citation